Natural habitat of Ipomoes aquatica and its invitro antimicrobial activity - Abd. Samah, Othman; Othman, Sarah Ilya; Hashim, Ridzwan (2010)
Ipomoea aquatica known as water convovulus or swamp cabbage is prolific in many parts of Asia. The plant species which might be a native to China is rich in nutrient and very popular among Asian cuisine. In Malaysia, Indonesia, Sri Lanka and Vietnam the plant is called kangkong whereas in Japan it is known as kankon. The plant has a crreping growth and it is well adapted to swampy land. It usually grows erect in an aquatic environment at optimum pH5.3-6.0 and it flourishes naturally in many waterways. In pond water the presense of 2.5-10.2 ppm dissolved oxygen and 0.04-2.3 ppm nitrates may help them to float. The plant acts as ecological threat because it forms dense floating mats of intertwined stems over water surfaces, shading ou native submerged plants competing with native emergents. Accumulation of heavy metals in Ipomoea aquatica has been reported in Asia because the plants often grow in plluted water. Comparatively, sewage polluted surface water contain greater numbers of bacteria than that in water supplies. We have evaluated the antimicrobial properties of Ipomoea aquatica using methanol and chloroform crude extracts of leaves and stems both by disc diffusion method and the minimum inhibitory concentration assay. All crude extracts demonstrated inhibition zones against certain species of pathogenic microorganisms such as Staphyloccucus aureus and Bacillus subtilis and Candida albican. The choloform crude extracts of stems are most active against Pseudomonas aeruginosa and Escherichia colo at concentrations of 50 and 20 mg/mL, respectively. However, in the methanol crude extracy of leaves it shows the highest inhibition zones of 8 mm, with minimum inhibitory concentration of 6.25 mg/mL against Staphylococcus aureus. Undoubtedly, natural compounds present in an aquatic plant such as Ipomoe aquatica could be considered a source of potential biological contro agents.